A comparative study on channel coding scheme for underwater acoustic communication - Ahmed, Mustafa Sami; Shah, Nor Shahida Mohd; Al-Aboosi, Yasin Yousif; Ghaleb, Ali Nadhim (Bulletin of Electrical Engineering and Informatics, 2023)
There are various challenges in underwater acoustic communication (UWA) however bit error rate (BER) is considered as the main challenge as it significantly affects the UWA communication. In this paper, different coding schemes such as convolution, turbo, low density parity check (LDPC), and polar coding based on the t-distribution noise channel are investigated, and binary phase-shift keying (BPSK) modulation with a code rate of 1/2 has considered in the evaluation and analyses. The evaluation of these channel coding schemes is performed based on BER, computational complexity as well as latency. The results have shown the outperform of polar coding in UWA over other channel coding schemes as it has lower BER and lower computational complexity.